Information Quality Activities within the Industry Initiative of Service-Oriented Architecture Implementation - Sulong, Muhammad Suhaizan; Koronios, Andy; Gao, Jing; Abdul-Aziz, Azlianor (2011)
Service-oriented architecture (SOA) offers a way to accommodate evolving information management needs in order to make business agile and flexible in pace with dynamic business conditions. Adopting, implementing and running SOA require significant attention and effort in order to deliver high-quality data and realise the full value of SOA. In this paper, we examine the information quality related issues that have been investigated in four case studies in Australia organisations in order to uncover the activities in regard to information quality within their initiatives of implementing SOA. These information quality activities that solve certain information quality issues therefore, can be readily established across any industry to support the building of high quality next generation SOA solutions.